Assessment of slaughterhouse-based measures as animal welfare indicators in fattening pigs - Hernandez, Rick Obrian; Romero, Marlyn H.; Sanchez, Jorge A. (Frontiers in Animal Science, 2023)
In recent years, there has been growing interest in the assessment of animal welfare in slaughterhouses. The aim of this study was to determine the effectiveness of slaughter-based measures as animal welfare indicators and evaluate the relationships between these indicators and the sociodemographic characteristics of livestock drivers and transport conditions for fattening pigs in a commercial slaughterhouse. A total of 1,161 heavy pigs (105.6 ± 14.15 kg), from 22 commercial farms, were evaluated. Pigs were assessed ante mortem, during lairaging, by evaluating the number, location, and color of skin lesions, tail length, and the presence or absence of biting lesions, lameness, cough, rectal or vaginal prolapse, and umbilical hernia. Pulmonary lesions, pleuritis, pericarditis, and liver lesions were also recorded postmortem. A descriptive analysis was performed on antemortem and postmortem indicators to estimate their prevalence, and the relationships among antemortem and postmortem indicators were analyzed using two multilevel mixed-effects models—a linear regression and a logistic regression analysis— with the farm of origin as a fixed effect. Cough was present in 18.9% (n = 219) of pigs, whereas the prevalence of tail biting lesions (4.6%, n = 53), rectal prolapse (0.1%, n = 11), and vaginal prolapse (0.1%, n = 11) was low. As regards lesion shape, linear lesions accounted for the majority of skin lesions (55.8%, n = 648), followed by comma-shaped (34.7%, n = 403), diffuse (6.9%, n = 80), and rectangular lesions (2.5%, n = 29). Only 25.2% (n = 512) of lesions were bright red. At postmortem, pulmonary lesions were noted in 34.2 ± 13.5 (mean ± SEM) pigs, and were more prevalent in the cranial (11.9 ± 4.9) and medium lobes (12.2 ± 5.2); the caudal (5.3 ± 2.7) and accessory lobes (1.6 ± 1.6) were less affected. The number of skin lesions was significantly associated with drivers’ age, job experience (years), and marital status (p ≤ 0.001). The presence or absence of tail lesions was strongly associated with the number of skin lesions, scoring of pulmonary lesions, and animal live weight (p ≤ 0.001). Antemortem and postmortem indicators at slaughterhouses with low annual slaughter volumes can provide key information for disease monitoring and animal welfare.